Distal Tibial Tuberosity Arc Osteotomy in Open-Wedge Proximal Tibial Osteotomy to Prevent Patella Infra - Akiyama, Takenori (Arthrosc Tech, 2019)
Open-wedge high tibial osteotomy is considered to be an effective surgical intervention for medial compartmental knee osteoarthritis. However, patella infra, which has been reported to be a result of tuberosity distalization after open-wedge high tibial osteotomy, changes the native patellofemoral biomechanics. This could raise abnormal patellofemoral contact stresses, which might be the trigger of patellofemoral arthrosis. To minimize the reduction in patellar height, we have developed a technique called open-wedge distal tuberosity tibial osteotomy. The benefits of this technique include increased bone-to-bone contact of the distal tuberosity cut surface after correction by cutting an arc osteotomy around the hinge position, which is the center of rotation. This technique also provides cortical support at the anterior osteotomy site without additional bone defect and, therefore, may be advantageous against weight-bearing stress on the osteotomy site. In all, open-wedge distal tuberosity tibial osteotomy could potentially be a unique open-wedge osteotomy that eliminates the risk for postoperative patellofemoral osteoarthritis and also could theoretically encourage rapid healing of the osteotomy, which could lead to early return to full physical activity.